A fuzzy gain-scheduler for the attitude control of an unmanned helicopter. - Kadmiry, B.
In this paper, we address the design of an attitude controller that achieves stable, and robust aggressive maneuverability for an unmanned helicopter. The controller proposed is in the form of a fuzzy gain-scheduler, and is used for stable and robust altitude, roll, pitch, and yaw control. The controller is obtained from a realistic nonlinear multiple-input-multiple-output model of a real unmanned helicopter platform, the APID-MK3. The results of this work are illustrated by extensive simulation, showing that the objective of aggressive, and robust maneuverability has been achieved.
Keywords: APID-MK3.; Takagi-Sugeno control; Altitude control; Attitude control; Fuzzy gain-scheduler.; Nonlinear multi-input multi-output model; Output-feedback control; Pitch control; Robust control; Roll control; Unmanned helicopter; Yaw control